THE INFLUENCE OF CAPITAL INTENSITY, FIRM SIZE, AND LEVERAGE ON TAX AVOIDANCE ON COMPANIES REGISTERED IN JAKARTA ISLAMIC INDEX (JII) PERIOD 2015-2019 - Nawang Kalbuana; Solihin Solihin; Yohana Yohana; Devia Rahma Yanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This research aims to find out the influence of capital intensity, firm size, and leverage on tax avoidance. This research is focused on companies listed in Jakarta Islamic Index (JII) period 2015-2019. The sample determination techniques used in this study are purposive sampling techniques and for data analysis using multiple linear analysis techniques. The results of the analysis show that capital intensity has a positive effect on tax avoidance, leverage negatively affects tax avoidance, and the size of the company has no effect on tax avoidance.